Subepithelial connective tissue graft for root coverage and histologic evaluation: clinical case reports - A Case Series - Menceva, Zaklina; Trajculeski, Stavre; Markovska Arsovska, Mirjana; Veleska Stevkovska, Daniela; Rusevska, Biljana; Spasovski, Spiro; Popovska, Mirjana (Medicinski časopis, 2025)
Abstract            The goal of periodontal surgery is to cover the exposed root completely or partially in teeth with gingival recession. This correction is important from an aesthetic and a functional point of view. Periodontal regeneration is visible only through histologic analysis. Histologic analysis can reveal the arrangement of the cells embedded in the periodontal-tissue attachment. Micro punch gum technique (2 mm) was used for biopsy. Three patients with gingival recessions were treated with subepithelial connective tissue graft (CTG) and clinical parameters and histological results were recorded. Complete coverage of the exposed root part was obtained in the three cases, and the histologic analysis revealed a selective settlement with ligament cells that are typical for the formation of connective tissue in periodontal regeneration. Histologic analysis showed keratinized sulcular epithelium with thin and tall extensions into the gingival connective tissue and a junctional epithelium which extended to new cementum. Also increased number of blood vessels and  new insertion of the connective tissue was observed. If the clinical goal of periodontal surgery is complete coverage of gingival recessions, then the goal at the microscopic level is to obtain true periodontal regeneration.Key words: gingival recession, elastic fibers, collagen fibers, connective tissue.
Keywords: gingival recession, elastic fibers, collagen fibers, connective tissue